Strategi Guru PAI dalam Menanamkan Nilai Kejujuran Melalui Keteladanan dan Pembiasaan di SDN Kemiri Sewu 1 Pandaan, Pasuruan - Mukhlis, Abdul (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2025)
This study aims to analyze the strategies of honesty value education based on teacher exemplarity and religious habituation at SDN Kemiri Sewu 1 Pandaan, Pasuruan, and to identify the supporting and inhibiting factors within the context of Islamic character education. Using a qualitative case study approach, data were collected through participatory observation, in-depth interviews with the principal, Islamic Education (PAI) teachers, and students, as well as documentation of daily religious activities. The data were analyzed descriptively through the stages of reduction, display, and verification. The findings indicate that teacher exemplarity is the core strategy in fostering honesty values through the hidden curriculum, where teachers’ behaviors such as discipline, integrity, and the courage to admit mistakes serve as moral models for students to emulate. Religious habituation through activities like salat dhuha, tadarus, and collective prayers acts as a reinforcing mechanism that strengthens moral awareness and internalizes honesty into daily behavior. The supporting factors include the principal’s leadership, the school’s religious environment, and positive emotional bonds between teachers and students. In contrast, inhibiting factors arise from family background diversity, digital media influence, and limited time allocation for formal PAI learning. This study concludes that the synergy between teacher exemplarity, religious habituation, and the school’s moral ecology effectively nurtures honesty as a spiritual and moral identity grounded in Islamic faith and practice. ABSTRACT  This study aims to analyze the strategies of honesty value education based on teacher exemplarity and religious habituation at SDN Kemiri Sewu 1 Pandaan, Pasuruan, and to identify the supporting and inhibiting factors within the context of Islamic character education. Using a qualitative case study approach, data were collected through participatory observation, in-depth interviews with the principal, Islamic Education (PAI) teachers, and students, as well as documentation of daily religious activities. The data were analyzed descriptively through the stages of reduction, display, and verification.The findings indicate that teacher exemplarity is the core strategy in fostering honesty values through the hidden curriculum, where teachers’ behaviors such as discipline, integrity, and the courage to admit mistakes serve as moral models for students to emulate. Religious habituation through activities like salat dhuha, tadarus, and collective prayers acts as a reinforcing mechanism that strengthens moral awareness and internalizes honesty into daily behavior. The supporting factors include the principal’s leadership, the school’s religious environment, and positive emotional bonds between teachers and students. In contrast, inhibiting factors arise from family background diversity, digital media influence, and limited time allocation for formal PAI learning. This study concludes that the synergy between teacher exemplarity, religious habituation, and the school’s moral ecology effectively nurtures honesty as a spiritual and moral identity grounded in Islamic faith and practice.